2014
DOI: 10.1103/physrevb.90.235115
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism of theFe2+andCe3+sublattices inCe2<

Abstract: The discovery of superconductivity in the 122 iron selenide materials above 30 K necessitates an understanding of the underlying magnetic interactions. We present a combined experimental and theoretical investigation of magnetic and semiconducting Ce2O2FeSe2 composed of chains of edgelinked iron selenide tetrahedra. The combined neutron diffraction and inelastic scattering study and density functional calculations confirm the ferromagnetic nature of nearest-neighbour Fe -Se -Fe interactions in the ZrCuSiAs-rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 79 publications
5
25
0
Order By: Relevance
“…This suggests that two magnetic ordering processes occur (ordering of Mn 2+ and ordering of Ce ). Similar behaviour has been observed in related systems 25,48 . Pawley refinement was used to confirm that all magnetic peaks could be indexed with the nuclear unit cell.…”
Section: 31supporting
confidence: 69%
“…This suggests that two magnetic ordering processes occur (ordering of Mn 2+ and ordering of Ce ). Similar behaviour has been observed in related systems 25,48 . Pawley refinement was used to confirm that all magnetic peaks could be indexed with the nuclear unit cell.…”
Section: 31supporting
confidence: 69%
“…1(d)] [14,15], while for the more electronegative M = Co 2+ analogue, 180°J 2 interactions * e.e.mccabe@kent.ac.uk dominate, leading to a magnetic structure with k vector k = ( 1 / 2 1 / 2 0) with in-plane moments and nn moments perpendicular to one another [18,19,21,22]. For M = Fe, Fe-Se-Fe J 2 interactions are ferromagnetic (FM) [10] (consistent with the FM chains of edge-linked FeSe 4 tetrahedra in Ce 2 O 2 FeSe 2 ) [23,24]. La 2 O 2 Fe 2 OSe 2 adopts a two-k-vector magnetic structure [k = ( 1 / 2 0 1 / 2 ) and k = (0 1 / 2 1 / 2 )] with in-plane moments directed along the Fe-O bonds, with FM J 2 and AFM J 2 interactions consistent with theory and nearest-neighbor moments orthogonal to one another [ Fig.…”
Section: Introductionmentioning
confidence: 88%
“…Ce-Fe oxyselenides, where ordered Ce moments are required to fit the diffraction data and persist to surprisingly high temperatures [4,6,7,11]. An excellent fit to the PND data is achieved using this type of model, and the refined profiles for 2+ .…”
Section: Model 5) the Observation Of Ce Ordering Is Consistent With mentioning
confidence: 95%
“…All three structures can be adopted by Ce 2 O 2 FeSe 2 by modifying the synthesis conditions [4,13]. McCabe et al reported the nuclear and magnetic structure of bulk layered α-Ce 2 O 2 FeSe 2 [4,6]; the space group of the nuclear structure is Imcb (72). Nitsche et al observed all three polymorphs (which they label as oI -, oA-and mC-Ce 2 O 2 FeSe 2 according to their symmetry) in single crystals grown at different temperatures [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation